The Digital Aspects of Educational Challenges: Readiness of After-School Educators to Apply Information and Communication Technologies - Narovlianska, Maryna; Lukatskyi, Yevhenii (Theoretical and Methodical Problems of Children and Youth Education, 2025)
The article presents the results of an empirical study on the level of readiness of educators in after-school education institutions of the tourism and local history profile to use information and communication technologies (ICT) in their professional activities. The study was conducted in spring–summer 2025 among educators from 22 regions of Ukraine, with 400 respondents participating (321 educators and 69 students-prospective educators). A conceptual model of educators’ readiness to use ICT is proposed, identifying key components of this readiness. The analysis focused on both integral indicators and specific components: psychological, operational-informational, and methodological readiness. The results are examined across age groups, educators’ experience, and professional positions. It was found that novice educators and part-time workers demonstrate higher levels of readiness to use ICT, whereas the greatest challenges are observed among club leaders and educators with more than twenty years of experience. A statistically significant negative correlation was revealed between educators’ age characteristics and their level of ICT readiness. A comparison was also made between the ICT readiness levels of senior students of pedagogical higher education institutions and in-service educators. The study concludes with the need for differentiated support programs for educators and emphasizes the importance of further developing educators’ digital competence within the postgraduate education system, as well as creating modern, effective forms of professional development.